1998
DOI: 10.2500/108854198778557719
|View full text |Cite
|
Sign up to set email alerts
|

An Allergy and Asthma Educational Outreach Program for School Nurses and Staff

Abstract: We conducted an educational outreach program for school nurses and staff based on survey findings from 73 schools in Indianapolis. The survey revealed the following main concerns school nurses had regarding the care of children with allergies and asthma: 1) lack of information (73%), 2) medication usage (73%), and 3) recognition and treatment of anaphylaxis (34%). Only seven (19%) of the responding schools had an allergy and asthma program. Less than half of the schools had policies dealing with anaphylaxis, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Of those students who had food-induced allergic reactions in school, 14% had no physician's order for treatment. Wu and Hill 16 surveyed school nurses from 47 schools in Indianapolis and found that 53% of the schools had no policy for management of anaphylaxis and the remaining 47% had a policy that consisted only of calling 911. Weiss et al 17 performed a national survey of 400 school nurses and found staff training was in place for 78%, 43% used guidelines provided by the state, and 32% followed guidelines developed by an outside organization.…”
Section: Inadequate Food Allergy Management Plansmentioning
confidence: 98%
“…Of those students who had food-induced allergic reactions in school, 14% had no physician's order for treatment. Wu and Hill 16 surveyed school nurses from 47 schools in Indianapolis and found that 53% of the schools had no policy for management of anaphylaxis and the remaining 47% had a policy that consisted only of calling 911. Weiss et al 17 performed a national survey of 400 school nurses and found staff training was in place for 78%, 43% used guidelines provided by the state, and 32% followed guidelines developed by an outside organization.…”
Section: Inadequate Food Allergy Management Plansmentioning
confidence: 98%
“…In a survey of school nurses representing 73 schools in Indianapolis, only 19% of the responding schools had an allergy program in place, and none were equipped with epinephrine. Only 62% of the nurses were willing to administer epinephrine in the event of an anaphylactic emergency (Wu & Hill, 1998).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Evidence dating back decades highlights the fact that schools are unprepared for medical emergencies, specifically anaphylaxis. 2 Various groups have set forth recommendations encompassing food policies and education for school staff in an attempt to address this need 3 ; however, as detailed in the article by Waserman et al, 1 there is no evidence that schools are any better prepared than they were 20 years ago. The disconnect between the studies published over a period of more than 20 years and the lack of evidence for any particular policy, not to mention the tremendous heterogeneity of policies that fill the evidence-void, signifies a perilous gap in the community between schools and medical professionals, particularly, allergists.…”
mentioning
confidence: 99%